The Bajada del Diablo astrobleme-strewn field, central Patagonia Argentina: Extending the exploration to surrounding areas - Acevedo, Rogelio Daniel (2012)
The Bajada del Diablo astrobleme-strewn field is a huge domain of enigmatic circular structures located in Central Patagonia. Three more localities are herein described, adding to the first area studied so far (Acevedo et al., 2009). Taking into consideration the four areas, a single, blurred crater dispersion ellipse has been identified. The four sectors have been now investigated, mapped and georeferred, and their circular structures,with a total of 189, some of them partially obliterated by erosion or sediment accumulation, were identified by remote sensing techniques, but many of them have been evaluated in situ and interpreted as impact craters. Moreover, two of the structures have been surveyed in detail in the field using a total station instrument. In addition to the previously known occurrence of circular structures on the Eruptive Complex Quiñelaf (Miocene basalts), the Pampa Sastre Fm. (Pliocene conglomerates) and the Pleistocene pediment gravels and sands, and the geomorphological inferences that have suggested the extraterrestrial origin of this event (since no other natural Earth surface process could be responsible of their formation), it should be now added the recurrent absence of the Pliocene stratigraphic unit at the bottom of the craters found on the pediment gravel and sands . Its removal has been interpreted as directly related to the impact, according to the magnetometric record of existing magnetic anomalies. Other preliminary observations on the collected samples, glass, breccias and, most relevant, Fe-Nibearing spherules picked up within the impact zones, are herein discussed. Two hypotheses have been put forward about the nature of the possible impacting object that formed these astroblemes which, fragmented in hundreds of pieces, hit the surface of the Earth perhaps in Middle Pleistocene times. One of them is related to a desintegrated asteroid of the rubble-pile type, whereas the second hypothesis refers to the collision of a split comet with the Earth surface, being this the most probable since no meteorite fragments have been found so far.